Pengaruh Rekrutmen Dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Dimensi Mandiri Teknologi - Yulistiani Solekha (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Information Technology is very important in driving progress and change in various fields. This forces every company to optimize all company assets, especially human resources. To get good human resources, recruitment and work discipline must be implemented well too. The purpose of this research is to determine the effect of recruitment and work discipline on employee performance at PT. Independent Dimension of Technology. The method used in this research is a quantitative method with primary data methods obtained from questionnaire data which is measured using a Likert scale. The population used in this research is employees of PT. Mandiri Technology Dimensions in the personnel division. The sample in this study used a saturated sample where all members of the population were sampled, namely 30 samples. Data collection uses questionnaires that are distributed directly. Data analysis techniques were processed using the IBM SPSS 25 for window application. Based on this research, it shows that recruitment (X1) has a positive and significant effect on employee performance (Y), work discipline (X2) has a positive effect on employee performance (Y), then simultaneously recruitment and work discipline have a significant effect on employee performance.